Lung microbiome and antibiotic resistome of cystic fibrosis patients attending clinics in the Gauteng Province, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2022)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2021.